Completeness of Medical Record Documents: Exploration on Causes and Solutions - Syukria, Orin Annahriyah; Wardhani, Viera (Jurnal Kedokteran Brawijaya, 2021)
The delay in returning inpatients' medical record documents (MRDs) to the medical records subdivision can cause some effects. This study was conducted to explore MRD completeness and the factors causing the delays in returning the document. This study used a descriptive observational method. Exploration was carried out on 21 MRDs using a checklist as an instrument. Besides, data were obtained through interviews involving the heads of related subdivisions and surveys on 52 nurses. Data were collected using an interview guide and a nursing work index-revised (NWI-R) instrument adapted into Indonesian. MRDs returned on time were complete in content and form than documents returned late to the medical records subdivision. One of the root causes of this problem is the officer factor, in this case is the nurse. The result of the NWI-R assessment is 3.15 (a maximum score of 4), meaning that the work environment in X Hospital supports nurses in carrying out their duties well. The highest score, 3.31, is the nurse-doctor relationship factor. The lowest value, 2.93, is the factor of resources adequacy to provide quality services. The possible solutions are to carry out routine briefings related to filling in and returning DRM followed by training.